Effect of sludge retention time on membrane bio-fouling using different type and pore size of membranes in a submerged membrane bioreactor. - Dizge, Nadir (Water Science and Technology)
The objective of this study was to investigate the influence of sludge retention time (SRT) on membrane bio-fouling. An activated sludge reactor was operated at three different SRTs (10, 30, and 50 days). Submerged membrane experiments were performed when the mixed liquor suspended solids (MLSS) concentration reached the steady state conditions. MLSS concentrations reached the steady state at 3,109 ± 194, 6,209 ± 123 and 6,609 ± 280 mg/L for SRTs of 10, 30 and 50 days, respectively. The total soluble microbial products (SMP) were 20.1 ± 3.7, 16.2 ± 7.2 and 28.2 ± 8.4 mg/L at SRTs of 10, 30, and 50 days, respectively. The carbohydrate concentration in the supernatant was about two times more for SRT of 10 days than that for 50 days. The total amount of extracellular polymeric substances (EPS) extracted from the flocs were approximately 74.9 ± 11.9, 67.8 ± 15.0 and 67.5 ± 17.4 mg/g MLSS at three SRTs (10, 30, and 50 days) under the same organic loading rate. The viscosity of the biomass increased with the increasing SRT. The results of flux stepping tests showed that the membrane fouling at SRT 10 days was always higher than that of 30 and 50 days. Four different microfiltration membranes (cellulose acetate, polyethersulfone, mixed ester, and polycarbonate) with three different pore sizes (0.45, 0.22, 0.10 μm) were tested. Filtration resistances were determined for each membrane. Cake resistance was observed to be the most significant fouling mechanism for all membranes.